Simple suture whipstitch closure is a reasonable option for many patients requiring temporary abdominal closure for blunt or penetrating trauma. Issue 1 (21st October 2022) - Collins, Reagan; Dhanasekara, Chathurika Samudani; Morris, Erin; Marschke, Brianna; Dissanaike, Sharmila
Abstract : Objectives: Multiple temporary abdominal closure (TAC) techniques are currently used to manage the open abdomen (OA) in severely injured trauma patients, with variability in efficacy and cost. We evaluated the clinical outcomes of two commonly used TAC methods: ABTHERA Negative Pressure Therapy System and whipstitch suture closure (WC). Methods: We conducted a retrospective review of patients who had blunt or penetrating trauma from 2015 to 2021 with OA managed using either ABTHERA, WC, or both. Primary outcomes included overall and intensive care unit length of stay, ventilator days, number of laparotomies, time to definitive fascial closure, and complications (bleeding, evisceration, wound dehiscence, and reoperation). Univariate and multivariate analyses were used to compare baseline characteristics, outcomes, and complications. Potential mediators of the relationship between the type of TAC and outcomes were explored using mediation analyses. Results: A total of 112 TAC were analyzed; 86 patients had a single type of TAC placement (either WC or ABTHERA), whereas 26 had both types. A majority of patients had blunt trauma in both WC (77%) and ABTHERA (76%) cohorts. There were no differences in baseline characteristics, including injury severity (27.5±12.4 and 27.5±12.0 for ABTHERA and WC, respectively). There was no statistically significant difference among individual complications and overall complications (OR=0.622 (0.274 to 1.412)). No differences were found between the outcomes, and any apparent differences seen were mediated by factors such as a higher number of laparotomies. Conclusion: WC is a low-cost option for TAC in trauma, with similar clinical outcomes and complications to ABTHERA. Level of evidence: Level III therapeutic/care management study.